PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) BADAN PENDAPATAN DAERAH KABUPATEN SITUBONDO MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Maltuf, Faqih; Karnadi, Karnadi; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2024)
The Regional Revenue Agency is a regional government organization that regulates and manages regional taxes and levies. The target population in this research is the civil servants of the Situbondo Regional Revenue Agency. There were 40 respondents in this study. The sampling technique used was simple random sampling. Data analysis and hypothesis testing in this research used the Partial Least Square - Structural Equation Model (PLS-SEM). Organizational culture, work environment, and work motivation are essential components in maintaining the stability of employee performance. This research aims to determine the influence of these factors on performance through job satisfaction as an intervening variable. The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that organizational culture has a positive but not significant effect on job satisfaction, the work environment has a positive but not significant effect on job satisfaction, work motivation has a negative but not significant effect on job satisfaction, organizational culture has a significant positive effect on performance, work environment has a significant positive effect on performance, work motivation has a negative but not significant effect on performance, and job satisfaction has a positive but not significant effect on performance. Then, the results of the indirect effect hypothesis test show that the organizational culture variable on performance through job satisfaction has a positive but not significant effect, the work environment on performance through job satisfaction has a positive but not significant effect, work motivation on performance through job satisfaction has a negative but not significant effect.